ANALISIS PENGARUH ORGANIZATIONAL CITIZENSHIP BEHAVIOR (OCB) TERHADAP PENINGKATAN MUTU PELAYANAN DI PUSKESMAS UJUNG KARANG BENGKULU TENGAH - Julianti Julianti; Henny Aprianty; Budiman Sakti (Yayasan Insani Mandiri Santani, 2025)
The quality of service at the Puskesmas (Community Health Center) is a measure of the quality of health services provided to the community. Good service quality is very important in ensuring equitable and effective health access, as well as increasing community satisfaction and health. The aim of this research is to analyze whether Organizational Citizenship Behavior (OCB) has a positive and significant effect on the improvement of service quality at Puskesmas Ujung Karang. This study uses a quantitative approach. The research will be conducted at Puskesmas Ujung Karang in Central Bengkulu Regency. This Puskesmas is located at Jl. Bengkulu - Kepahiang, Ujung Karang, Karang Tinggi District, Central Bengkulu Regency, Bengkulu. The research sample consists of 17 staff members from Puskesmas Ujung Karang (the entire population is taken because the total is less than 100) and 80 patients who have received services at Puskesmas Ujung Karang. In this research, the researcher used questionnaire and documentation data collection techniques. The results of the study indicate that there is an influence of Organizational Citizenship Behavior (OCB) on the improvement of service quality at the Ujung Karang health center, with a t value greater than the t table value. This means that the higher the OCB behavior demonstrated by employees (such as helping colleagues, being loyal to the organization, and taking initiative beyond their main duties), the higher the quality of service provided to the community will be. The correlation coefficient value (R = 0.587) indicates a strong relationship between OCB and service quality. This value falls within the range of 0.50–0.70, which is typically categorized in statistical interpretation as a moderate to strong relationship. This indicates that although there are other factors that may affect service quality, the contribution of OCB is quite significant and cannot be ignored. Keywords: Service Quality Improvement, Organizationional Citizenship Behavior (OCB), Puskesmas Ujung Karang